Translation regulation and RNA granule formation after heat shock of procyclic form trypanosoma brucei: many heat-induced mRNAs are also increased during differentiation to mammalian-infective forms - Minia, Igor; Mercé, Clémentine; Terrao, Monica; Clayton, Christine (PLoS neglected tropical diseases, 2016)
African trypanosome procyclic forms multiply in the midgut of tsetse flies, and are routinely cultured at 27°C. Heat shocks of 37°C and above result in general inhibition of translation, and severe heat shock (41°C) results in sequestration of mRNA in granules. The mRNAs that are bound by the zinc-finger protein ZC3H11, including those encoding refolding chaperones, escape heat-induced translation inhibition. At 27°C, ZC3H11 mRNA is predominantly present as an untranslated cytosolic messenger ribonucleoprotein particle, but after heat shocks of 37°C—41°C, the ZC3H11 mRNA moves into the polysomal fraction. To investigate the scope and specificities of heat-shock translational regulation and granule formation, we analysed the distributions of mRNAs on polysomes at 27°C and after 1 hour at 39°C, and the mRNA content of 41°C heat shock granules. We found that mRNAs that bind to ZC3H11 remained in polysomes at 39°C and were protected from sequestration in granules at 41°C. As previously seen for starvation stress granules, the mRNAs that encode ribosomal proteins were excluded from heat-shock granules. 70 mRNAs moved towards the polysomal fraction after the 39°C heat shock, and 260 increased in relative abundance. Surprisingly, many of these mRNAs are also increased when trypanosomes migrate to the tsetse salivary glands. It therefore seems possible that in the wild, temperature changes due to diurnal variations and periodic intake of warm blood might influence the efficiency with which procyclic forms develop into mammalian-infective forms.
Gesehen am 19.05.2020